UCP2 Modulates Cardioprotective Effects of Ru360 in Isolated Cardiomyocytes during Ischemia - Lukas J. Motloch; Sara Reda; Martin Wolny; Uta C. Hoppe (MDPI AG, 2015)
Introduction: Ruthenium 360 (Ru360) has been shown to induce cardioprotective mechanisms in perfused hearts. The agent is a specific blocker of the main cardiac mitochondrial uptake mechanism, the mitochondrial calcium uniporter (MCU). UCP2, a mitochondrial membrane protein, which influences cardiac ROS formation was reported to interact with the MCU. Methods: To prove whether Ru360 affects ischemic cell injury on the singular cell level, cell viability (CV) in isolated cardiomyocytes from wild type mice (WT) was measured in a model of pelleting hypoxia (PH). To explore a possible influence of UCP2 on cellular survival, as well as on Ru360 function, cardiomyocytes from UCP2−/− mice were investigated. Results: During PH, Ru360 significantly improved CV in WT cardiomyocytes (Control 26.32% ± 1.58% vs. PH 13.60% ± 1.20% vs. PH+Ru360 19.98% ± 0.98%, n = 6; p < 0.05). No differences in the rate of apoptosis were observed in UCP2−/− vs. WT. In UCP2−/− cardiomyocytes, Ru360 reduced the rate of cell death. However, the effect was less pronounced compared to WT cardiomyocytes. Conclusion: Ru360 significantly reduces hypoxic cell injury by preventing single cell apoptosis in WT cardiomyoctes. UCP2 does not affect cell survival in hypoxic cardiomyocytes, but it might modulate cardioprotective effects of Ru360 during ischemia.